2002
DOI: 10.1080/00015550260132460
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rice Starch as a Bath Additive on the Barrier Function of Healthy but SLS-damaged Skin and Skin of Atopic Patients

Abstract: Rice starch added to bath water was studied for its possible beneficial effects on impaired barrier function as evaluated by transepidermal water loss measurements. The forearm skin of healthy volunteers was irritated by sodium lauryl sulphate. Exposure to rice-starch-containing bath water--twice daily for 15 min--led to a 20% improvement on the healing capacity of damaged skin. The beneficial effect was also observed for a rice-starch-containing lipid-free bath formulation, and an oil-in-water bath lotion enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 2 publications
0
13
0
2
Order By: Relevance
“…Addition of rice starch to bath water was recently shown to improve barrier function in patients with AD. 7 To prevent evaporative effects, which are damaging to the skin barrier, patients need to apply medication or moisturizer immediately after bathing or wetting their skin.…”
Section: Skin Hydration and Moisturizersmentioning
confidence: 99%
“…Addition of rice starch to bath water was recently shown to improve barrier function in patients with AD. 7 To prevent evaporative effects, which are damaging to the skin barrier, patients need to apply medication or moisturizer immediately after bathing or wetting their skin.…”
Section: Skin Hydration and Moisturizersmentioning
confidence: 99%
“…Current studies demonstrated that skin barrier dysfunction could be responsible for the pathogenesis of AD in a murine model and AD patients [24, 25]. Several studies have shown that treatment with a moisture cream could ameliorate the impairment of the skin barrier function in AD patients [26, 27]. Of interest, the density of S. aureus on the skin of the mice treated with Pet+UVA was lower at 17 weeks compared with that at the beginning of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted on volunteer subjects has shown that baths with rice starch can alleviate skin irritation caused by sodium lauryl sulfate (SLS), while they also ameliorate the skin barrier in patients with atopic dermatitis (Fujiwaki and Furusho 1992;De Paepe, Hachem et al 2002). Rice starch is also used in makeup products (Braunagel and Guderjahn 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 98%